Health Care Access and Physical and Behavioral Health Among Undocumented Latinos in California. Issue 11 (November 2018) - Ortega, Alexander N.; McKenna, Ryan M.; Kemmick Pintor, Jessie; Langellier, Brent A.; Roby, Dylan H.; Pourat, Nadereh; Vargas Bustamante, Arturo; Wallace, Steven P.
Abstract : Background: This paper provides statewide estimates on health care access and utilization patterns and physical and behavioral health by citizenship and documentation status among Latinos in California. Methods: This study used data from the 2011–2015 California Health Interview Survey to examine health care access and utilization and physical and behavioral health among a representative sample of all nonelderly Latino and US-born non-Latino white adults (N=51, 386). Multivariable regressions estimated the associations between the dependent measures and citizenship/documentation status among Latinos (US-born, naturalized citizen, green card holder, and undocumented). Results: Adjusted results from multivariable analyses observed worse access and utilization patterns among immigrant Latinos compared with US-born Latinos, with undocumented immigrants using significantly less health care. Undocumented Latinos had lower odds of self- reporting excellent/very good health status compared with US-born Latinos, despite them having lower odds of having several physical and behavioral health outcomes (overweight/obesity, physician-diagnosed hypertension, asthma, self-reported psychological distress, and need for behavioral health services). Among those reporting a need for behavioral health services, access was also worse for undocumented Latinos when compared with US-born Latinos. Conclusions: Patterns of poor health care access and utilization and better physical and behavioral health are observed across the continuum of documentation status, with undocumented immigrants having the worst access and utilization patterns and less disease. Despite fewer reported diagnoses and better mental health, undocumented Latinos reported poorer health status than their US-born counterparts.